Cloning and Characterization of a cDNA Encoding Murine Coagulation Factor X - Liang, Zhong; Cooper, Adrian; DeFord, Melanie E.; Carmeliet, Peter; Collen, Desire; Castellino, Francis J.; Rosen, Elliot D. (Thrombosis and Haemostasis, 1998)
The cDNA encoding murine coagulation factor X (fX) was isolated and reconstructed from a λZap cDNA library generated from murine liver mRNA. The cDNA contains 1486 bases starting at the 5’-translation initiation codon. It includes an open reading frame of 1443 nucleotides, followed by an 18 residue 3’ nontranslated sequence downstream of the first stop codon, and a 3’ poly(A) tail. The translation product is composed of a 40-amino acid signal/propeptide region followed by a 441-residue mature protein. The latter is highly homologous to that of human and rat fX. All protein domains of human and rat fX are strictly conserved in mouse fX. The cDNA coding for mouse fX has been expressed in human embryonic kidney 293 cells and generates fX activity measured in a clotting assay using human fX-deficient plasma.